Progress of research on methods of human resource allocation in operating room nursing - Zhang, Qiaoling; Yu, Bijun; Ou, Yangle; Zhou, Xiuran; Zou, Shifang; Peng, Hui; Yan, Xiaoying; Shen, Tiemei (Frontiers in Public Health, 2025)
The operating room is one of the most critical departments in a hospital, and the allocation of human resources for operating room nursing has a critical impact on operating room operations and surgical quality. This review systematically reviews current research on the content and methods of operating room nursing human resource allocation, including the quantity allocation, structure and quality allocation of operating room nursing human resources, and describes the specific operation, advantages and disadvantages of each allocation method, to provide a reference basis for the construction of a rationalized operating room nursing human resource allocation system.